Quantum Communication Technologies for Future Distributed Notification Systems - Ankita Kamat, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative potential of quantum communication technologies in revolutionizing distributed notification systems. The article examines the fundamental principles of quantum communication, including quantum key distribution and entanglement-based messaging, addressing their application in secure notification delivery. The article encompasses the limitations of classical systems while highlighting quantum advantages in security, efficiency, and reliability. Through detailed analysis of implementation challenges, technical solutions, and industry-specific applications across defense, healthcare, and financial sectors, the article provides insights into practical deployment strategies. The article also outlines a clear roadmap for adoption, from immediate implementation goals to long-term vision, while identifying crucial areas for future research and development in quantum network architecture and protocols.
Keywords: Entanglement Distribution; Quantum Communication; Quantum Key Distribution; Quantum Networks; Security Protocols